Psychoanalysis and child-rearing in twentieth-century France: the career of Françoise Dolto - Bates, Richard (2017)
This thesis is a critical introduction to the ideas and public influence of French child psychoanalyst Françoise Dolto (1908-88). In the late twentieth century Dolto was a figure of significant cultural importance in France, seen as the country’s leading authority on child psychology. The thesis approaches her career from the perspective of social and cultural history. It historicises Dolto’s resonance with wider French society, explains the intellectual genealogy of her ideas, and explores the societal implications of her fame. It constitutes a substantial contribution both to the history of psychoanalysis ‘beyond the couch’, and to the socio-cultural history of twentieth-century France.